Importance of gene mutation analysis as prognostic factor of acute myeloid leukemia - Yamaguchi, Hiroki (Rinshō ketsueki, 2020)
In acute myeloid leukemia (AML), a number of chromosomal abnormalities and gene mutations associated with onset and recurrence were discovered by the recent progress of genome analysis technology. The founding did not only have clinical application as prognostic factors and minimal residual disease markers but also contributed to novel molecular targeted drug development. Many new drugs, such as first-generation FLT3 inhibitor, IDH1/2 inhibitor, and BCL2 inhibitor, have been developed in Europe and the United States. In addition, the second-generation FLT3 inhibitors, gilteritinib and quizartinib, were developed in Japan, which significantly improved the treatment outcome of AML. However, there is still a large disparity in drug availability between Europe and the United States and Japan. As a result, treatment guidelines in Europe and the United States cannot be applied to practical use in Japan. This paper presents an outline of the prognosis stratification and indication of allogenic hematopoietic cell transplantation for AML by gene diagnosis in Japan.